Profitability, Leverage, and Sales Growth: The Mediating Role of Dividend Policy in Determining Firm Value - Ni Putu Diah Kartini; I Gde Ary Wirajaya (E-Jurnal Akuntansi, 2025)
Firm value represents the market's perception of a company's performance and future prospects. This study seeks to provide empirical evidence on the impact of profitability, leverage, and sales growth on firm value, with dividend policy serving as a mediating variable. The research sample comprises 60 energy companies selected from a population of 87 firms listed on the Indonesia Stock Exchange during the 2022–2023 period. Data were analyzed using path analysis techniques, employing SmartPLS 4.0 to evaluate the proposed relationships. The findings indicate that profitability, sales growth, and dividend policy positively influence firm value, whereas leverage exerts a negative effect. Moreover, profitability and sales growth positively affect dividend policy, while leverage has a negative impact. Dividend policy is shown to partially mediate the relationships between profitability and leverage with firm value, and fully mediates the relationship between sales growth and firm value.